(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: The study described some factors related to simple febrile seizures (SFS) in children from 6 months to 5 years old who were treated at Nam Dinh Children’s Hospital from September 2022 to August 2023. Subjects and methods: The study described a series of cases using the convenience sampling method, with a total sample size of all patients who met the research criteria. Results: The study was conducted on 166 children with SFS and 250 children in the control group (who had fever but no seizures). The likelihood of having SFS in children with a history of febrile seizures was 2.68 times (95% CI: 1.45-4.95) higher than in the group of children without this history (p=0.02). The likelihood of having SFS in children with a family history of febrile seizures was 3.48 times higher (95% CI: 1.18-10.20) than in children without a family history of febrile seizures (p=0.032). There were no significant differences in changes in white blood cell count, neutrophil count, and serum CRP between the two study groups. Conclusion: Children with a personal history of febrile seizures had a clearly higher chance of having a recurrence of SFS than children without this history. When a child had a fever, it was necessary to pay attention to the history of febrile seizures in the family, especially febrile seizure in close relatives, so that measures could be taken to prevent seizures due to fever in the child.